Validity of session rating of perceived exertion in Singaporean youth football players - Andi, Agus Salam Kahar (Nanyang Technological University, 2021)
Background: The intensified competitive demand of modern football induces greater importance in the management of training load (TL) for optimal training adaptation and recovery time for players. Monitoring TL is crucial for athletic development as well as injury prevention and fatigue management. No study has investigated the validity of session-RPE method to monitor TL for Asian youth athletes. Purpose: The aim of the study is to investigate the validity of session-rating of perceived exertion (session-RPE) in Singaporean youth football players by examining the correlation between Edwards’ training impulse (TRIMP) and session-RPE method of determining TL. Methods: Heart rate (HR) data were collected from 14 male football players (age = 14.0 ± 0.9) during four training. HR data were recorded using Polar H10 devices and Polar M430 watches, and RPE was collected 10 minutes after the end of the sessions. Pearson correlation coefficient was used to analyse the relationship between Edwards’ TRIMP and session-RPE. Results: Only data of seven participants were analysed. Between-participant analysis reported no significant correlation between Edwards’ TRIMP and session-RPE (r = .65, p > 0.05). Within-participant correlations were also found to be non-significant (r = -.25 to .98, p > 0.05). Conclusion: The finding could not verify the validity of session-RPE as a tool to monitor TL for Singaporean youth football players. Future studies could further investigate the validity of the method for Singaporean youth athletes in other sports.